DRUG UTILIZATION PATTERN IN OUTDOOR PATIENTS OF OPHTHALMOLOGY DEPARTMENT AT A TERTIARY CARE HOSPITAL IN SOUTHERN RAJASTHAN - SINGH, VIKRAM; ATRAY, MEENA; MEHANT, ASHISH KUMAR; PANCHOLI, DEVANG (International Journal of Current Pharmaceutical Research, 2026)
Objective: This study aimed to analyse the drug utilization pattern among outdoor patients in the Ophthalmology department at a tertiary care hospital in southern Rajasthan, with a focus on demographics, diagnosis, drug classes, and routes of administration. Methods: An observational study was conducted at Maharana Bhopal Hospital, Udaipur, over 12 mo from July 2024 to June 2025. Prescriptions from 386 patients aged 18 to 60 y were reviewed, recording drug name, dosage form, frequency, route, and duration. Data was analysed using WHO core prescribing indicators. Results: A total of 783 drugs were prescribed in 386 prescriptions, with an average of 2.02 drugs per prescription. The mean age of participant was 41.1 y, with males (53.6%) slightly outnumbering females. The most common diagnoses were allergy, cataract, and dry eye. Ocular lubricants (91.7%) and antimicrobials (57.5%) were the most frequently prescribed drug classes. Eye drops were the predominant dosage form (99.2%). The ophthalmic route was overwhelmingly preferred, supporting localized therapy in ocular conditions. Conclusion: Prescribing patterns were largely rational, with a focus on matching drug selection to specific diagnoses and prioritizing topical therapy. Continued audit and prescriber sensitization are recommended to ensure optimal drug utilization and improve patient outcomes in ophthalmic practice.